Enhancing humanistic development in young generation: an alternative youth program to regain harmony in post-modern society - Rashid, Ungaran (International Institute For Muslim Unity, 2023)
In a world brimming with diversity and unique perspectives, the importance of instilling ethical values in the heart and minds of the youth cannot be overstated. This topic embarks on a journey to nurture thirteen fundamental ethical values. Organised in three cohesive sections: being at peace barriers to peace, and ways to promote peace. This module represents a comprehensive approach to cultivating virtues that resonate with harmony and understanding.